PROFIL KEMAMPUAN MAHASISWA CALON GURU BIOLOGI DALAM MENGOMUNIKASIKAN HASIL PRAKTIKUM FISIOLOGI HEWAN - Astuti, Yuni; Suciati, R. (Jurnal Pendidikan Indonesia, 2017)
The main problem in this research is to analyze the profile communications skill of Biology’s student teachers in preparing the report practicum course on Animal Physiology. The research method used is descriptive quantitative method. Data (score of practical reports) is averaged then analyzed descriptively. The results are the ability of prospective biology teacher in communicating the practical results fall into the category enough and tends to increase. Mean score of practical report 1, 2, and 3 respectively 1.72; 2.03;  2.31. In addition, aspects of assessment "are precision systematic writing lab report" increased. Preparation of practical reports are in accordance with the systematics of good writing. Aspects of assessment "ability to process data accurately findings" and "relevance of theories in analyzing the data findings" also increased, with the average score of each is 1.10 to 2.27 and 1.27 to 2.17. So it can be concluded that a prospective biology teacher communication skills in the preparation of practical reports on subjects Physiology categorized enough. Giving feedback is considered effective in improving the ability of it.